2013
DOI: 10.1371/journal.pone.0078520
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Polymorphisms and Environmental Smoke Exposure as Risk Factors for Oesophageal Squamous Cell Carcinoma

Abstract: MicroRNAs (miRNAs) and related polymorphisms have been implicated in the susceptibility to oesophageal squamous cell carcinoma (OSCC). In our study, three miRNA-related SNPs: rs6505162 A>C (pre-miRNA of miR-423), rs213210 A>G (3’UTR of miR-219-1) and rs7372209 C>T (5’UTR of miR-26a-1) were investigated in the Black and Mixed Ancestry population groups in South Africa. The potential cumulative effects of these SNPs, as well as gene-environment interactions were also analysed. In Blacks, rs6505162 A>C was associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 37 publications
0
48
0
Order By: Relevance
“…Two studies concluded that the A allele of the rs6505162 increased the risk of breast cancer, [22, 24] whereas the same allele presented a decreased risk of developing lung cancer and bladder cancer in two other studies [30, 32]. The inconsistent effect for the A allele was also observed among three esophageal cancer studies [2628]. Meta-analysis, as a powerful statistical method, could provide a quantitative approach for pooling the results of different studies on the same topic and estimating the diversity.…”
Section: Discussionmentioning
confidence: 98%
“…Two studies concluded that the A allele of the rs6505162 increased the risk of breast cancer, [22, 24] whereas the same allele presented a decreased risk of developing lung cancer and bladder cancer in two other studies [30, 32]. The inconsistent effect for the A allele was also observed among three esophageal cancer studies [2628]. Meta-analysis, as a powerful statistical method, could provide a quantitative approach for pooling the results of different studies on the same topic and estimating the diversity.…”
Section: Discussionmentioning
confidence: 98%
“…There are no published data on the genetics and risk factors for OSCC in Zambia, although in studies within the region (South Africa and Uganda), smoking has been reported to play a major role in esophageal cancer 3 , 31 , 33 . However, there is a need to further evaluate the relationship between gene susceptibility and lifestyle risk factors such as smoking 34 . We found a highly significant association between cigarette smoking and OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Carcinogenesis and development of ESCC are complex biological processes involving multiple factors, including environmental risk factors. ESCC is a polygenic hereditary disease that can also be influenced by genetic factors [ 5 , 14 , 30 , 31 ]. Along with other researchers, we have long carried on the etiological and epidemiological investigation of numerous aspects of the high Kazakh ESCC incidence rate, which may include traditional habits and customs, such as eating hot meals, hard foods, yogurt knots, and tea; smoking; lack of folic acid; natural geographical environment [ 31 ]; genetic factors, such as PLCE1, hRFT1, and ECRG2 [ 14 , 32 , 33 ]; and microbial factors, such as HPV [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…SNP in miRNA genes, a common type of genetic variation in the human genome, was associated with different types of cancer susceptibility [ 5 , 15 , 26 , 35 ], as SNP can play a predictive role in the risk of cancer development and clarify the pathophysiological mechanism of carcinogenesis. Several studies have linked the miR-219-1 SNP to cancer susceptibility [ 24 , 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation